Icelandic Folklore and the Cultural Memory of Religious Change - Bryan, Eric Shane (Borderlines, 2021)
Frontmatter -- CONTENTS -- Preface -- Acknowledgements -- Introduction: Stories, Memories, and Mechanisms of Belief -- Chapter 1. The Dead Bridegroom Carries Off His Bride: Pejoration and Adjacency Pairs in ATU 365 -- Chapter 2. The Elf Woman’s Conversion: Memories of Gender and Gender Spheres -- Chapter 3. The Fylgjur of Iceland: Attendant Spirits and a Distorted Sense of Guardianship -- Chapter 4. The Elf Church: Memories of Contested Sacred Spaces -- Chapter 5. The Stupid Boy and the Devil: Sæmundur Fróði Sigfússon, Magic, and Redemption -- Conclusion -- Select Bibliography -- Index